2010
DOI: 10.3109/02844310903528697
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome and treatment of recurrent symptoms

Abstract: Carpal tunnel syndrome is the most common compression lesion of peripheral nerves with a prevalence of 4%. It is often treated by release of the flexor retinaculum, which may completely relieve the symptoms. Although such treatment is considered successful, there are probably many patients with persistent or recurrent symptoms. Recurrence implies that the patient's symptoms were initially relieved but recurred some time after the operation; this is a controversial field in which clear definitions, aetiology, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Treatment of recurrent CTS is challenging, and several procedures have been reported to prevent re‐recurrence of the disease. Hypothenar fat pad is the most commonly used local flap to cover the median nerve for recurrent CTS . However, its coverage of the median nerve is sometimes not sufficient and re‐recurrence rate of CTS is high; the procedure is often ineffective for the treatment of cases with severe pain, such as CRPS type II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of recurrent CTS is challenging, and several procedures have been reported to prevent re‐recurrence of the disease. Hypothenar fat pad is the most commonly used local flap to cover the median nerve for recurrent CTS . However, its coverage of the median nerve is sometimes not sufficient and re‐recurrence rate of CTS is high; the procedure is often ineffective for the treatment of cases with severe pain, such as CRPS type II.…”
Section: Discussionmentioning
confidence: 99%
“…Simple re‐CTR and dissection of adhesion surrounding the median nerve is rarely effective in recurrent CTS . Local or free flaps are used to prevent the adhesion of the surrounding tissue to the median nerve . Treatment of recurrent CTS with severe pain, especially one with a neuroma‐in‐continuity, is challenging .…”
mentioning
confidence: 99%
“…There are at least 16 possible interventions for CTS with varying levels of evidence to support their use [13]. Surgical treatment is considered the most effective treatment for severe CTS [14] but is a less-than-optimal initial approach for people with mild-to-moderate CTS because of the potential for adverse events [15], recurrence [16], and high medical costs [17,18]. A recent international multidisciplinary treatment guideline [12] has suggested that treatment should be based on the duration and severity of the CTS and advocated for combinations of education, splinting, and steroids, with surgery provided for those with severe CTS or who did not respond well to conservative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Neural adhesion of superficial radial nerve sometimes occurs when scar tissue adheres to the damaged nerve. This condition is characterized by dysesthesia and pain radiating to the nerve‐innervated area during wrist and thumb motion . Definitive diagnostic criteria for neural adhesion have not yet been established and thus diagnosis might be difficult clinically.…”
mentioning
confidence: 99%
“…This condition is characterized by dysesthesia and pain radiating to the nerve-innervated area during wrist and thumb motion. [8][9][10][11] Definitive diagnostic criteria for neural adhesion have not yet been established and thus diagnosis might be difficult clinically. Some surgeons have reported that recurrent adhesion after neurolysis is not uncommon, but great care should be taken in operations for neurolysis because of the unreliable outcomes.…”
mentioning
confidence: 99%